A Comparative Analysis of the Concept of Heartbreak in the Lyrics of Songs by Gilga Sahid and Happy Asmara - Dewi Kusumaningsih; Rahma Fatiya; Benedictus Sudiyana; Wahyu Dini Septiari; Susi Darihastining (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2025)
Heartbreak songs serve as a poignant portrayal, resonating with the realities of everyday life or drawing from the personal experiences of the lyricists. In this regard, this research aimed to compare the conceptualization of heartbreak in the lyrics of songs composed by Gilga Sahid and Happy Asmara, focusing on differences in vocabulary choices, terms, similes, and language styles, conveying the meaning of heartbreak in their respective songs. The present study employed a qualitative descriptive design to investigate Javanese dangdut songs by Gilga Sahid and Happy Asmara. Data were collected from fragments of song lyrics that encapsulate the essence of heartbreak. Documentation, listening, and note-taking were utilized to scrutinize various sources, ensuring the credibility of the findings. The data analysis process incorporated descriptive analysis techniques, elucidating disparities in vocabulary choices and sentence structure patterns within the song lyrics. The findings highlighted distinctions between the two artists regarding their vocabulary choices and sentence structures. These dissimilarities contributed to the distinctive characteristics of their songs, involving symbolic elements to convey meaning and occasionally prompting code-switching events in the lyrics, given the Javanese dangdut genre under investigation. Including symbolic elements in the lyrics further enriched the depth of meaning within the songs. It is hoped that this research will have benefits in the fields of language and culture.